Neoadjuvant chemoradiation alters the immune microenvironment in pancreatic ductal adenocarcinoma. (31st December 2022) - Gartrell, Robyn D.; Enzler, Thomas; Kim, Pan S.; Fullerton, Benjamin T.; Fazlollahi, Ladan; Chen, Andrew X.; Minns, Hanna E.; Perni, Subha; Weisberg, Stuart P.; Rizk, Emanuelle M.; Wang, Samuel; Oh, Eun Jeong; et al.
ABSTRACT: Patients with pancreatic ductal adenocarcinoma (PDAC) have a grim prognosis despite complete surgical resection and intense systemic therapies. While immunotherapies have been beneficial with many different types of solid tumors, they have almost uniformly failed in the treatment of PDAC. Understanding how therapies affect the tumor immune microenvironment (TIME) can provide insights for the development of strategies to treat PDAC. We used quantitative multiplexed immunofluorescence (qmIF) quantitative spatial analysis (qSA), and immunogenomic (IG) analysis to analyze formalin-fixed paraffin embedded (FFPE) primary tumor specimens from 44 patients with PDAC including 18 treated with neoadjuvant chemoradiation (CRT) and 26 patients receiving no treatment (NT) and compared them with tissues from 40 treatment-naïve melanoma patients. We find that relative to NT tumors, CD3 + T cell infiltration was increased in CRT treated tumors (p = .0006), including increases in CD3 + CD8 + cytotoxic T cells (CTLs, p = .0079), CD3 + CD4 + FOXP3 − T helper cells (Th, p = .0010), and CD3 + CD4 + FOXP3 + regulatory T cells (Tregs, p = .0089) with no difference in CD68 + macrophages. IG analysis from micro-dissected tissues indicated overexpression of genes involved in antigen presentation, T cell activation, and inflammation in CRT treated tumors. Among treated patients, a higher ratio of Tregs to total T cells was associated with shorter survival time (p = .0121). Despite comparable levels of infiltrating T cells in CRT PDACs to melanoma, PDACs displayed distinct spatial profiles with less T cell clustering as defined by nearest neighbor analysis (p < .001). These findings demonstrate that, while CRT can achieve high T cell densities in PDAC compared to melanoma, phenotype and spatial organization of T cells may limit benefit of T cell infiltration in this immunotherapy-resistant tumor.